Comment on "The challenge of energy-efficient transportation" J. Hermans. (5th June 2017) - Rez, Peter
ABSTRACT: It's hard to beat the energy density and convenience of liquid hydrocarbons. The product of energy used and journey time is another way to compare transportation systems. It is more practical to power electric cars from batteries than photovoltaics. Solar can be used to supply some of the energy needed to recharge the batteries. The primary energy used to make food, the fuel for the human cyclist, can be many times the calorific energy derived from the food. Transportation is a major source of carbon dioxide emissions. Hermans makes some excellent points in his article "The challenge of energy-efficient transportation." However primary energy to produce fuel should also be considered. The embodied energy of liquid hydrocarbon fuels is much less than their energy content. For a cyclist the fuel is food, and, depending on diet, the primary energy can be many times the food's calorific energy. The article is over optimistic on the prospect of cars directly powered by solar photovoltaics. It's more realistic to use batteries in electric cars and generate the electricity from a number of sources. For anything other than trains that run on fixed tracks it's hard to beat the energy density and convenience of liquid hydrocarbons.